Incorporating aspects of motor control in the optimisation of human performance - Hiley, M. J. (Science et motricité, 2012)
Computer simulation modelling is a powerful tool in Sports Biomechanics as it allows the researcher to investigate the underlying mechanics of technique. Once the underlying mechanics have been established technique may be optimised, which may be used to reduce injuries or to improve performance. When optimising technique, minimising effort or joint torque is often used as the basis of the score (or cost function). Many tasks in everyday life may be based on minimising such variables, however, in the field of sport it is often the case that effort is maximised in order to achieve the desired aspect of technique or to achieve the performance outcome. Therefore, optimisation criteria must reflect the performance outcome rather than the amount of effort required. It is acknowledged that realistic strength characteristics should be incorporated in to simulation models so as to be representative of the athlete, however, strength should not be considered the only limit to maximal performance. Aspects of motor control such as coordination and timing precision are as, if not more, important in certain limiting situations. The aim of this paper is to demonstrate how computer simulation modelling may be used to gain an insight into the important aspects of gymnastics swinging techniques and the importance of including aspects of motor control when investigating limiting movements. The paper presents three case studies to outline the above issues.